Fish Collagen Promotes the Expression of Genes Related to Osteoblastic Activity - Mark Luigi Fabian Capati; Ayako Nakazono; Kohei Yamamoto; Kouji Sugimoto; Kajiro Yanagiguchi; Shizuka Yamada; Yoshihiko Hayashi (International Journal of Polymer Science)
Tilapia type I atelocollagen (TAC) is a strong candidate for clinical application as its biological scaffold due to a high degeneration temperature and biologically safe properties. The aim of this study was to confirm the biological effects of TAC in vitro on osteoblastic cells, simulating its clinical application. The proliferation and differentiation of typical preosteoblasts, MC3T3-E1 cells, were investigated using a microarray analysis, staining assay for mineralization, and real-time PCR analysis of the expression of mineralization-related genes. The mRNA expression of 10 genes involved in proliferation and differentiation increased after 3-day culture on an TAC gel, with an average balanced score ratio exceeding 1.5 compared to the control. After two weeks of culture, all three experimental groups showed stronger alkaline phosphatase staining than after one week. The genes expression of alkaline phosphatase, osteocalcin, and bone sialoprotein increased under the experimental conditions. The gene expression of osteopontin did not increase, and no statistical differences were noted among the three experimental groups. The present and previous findings suggest that TAC is not only a suitable alternative to collagen products originating from mammals but also a novel biomaterial with cell differentiation ability for regenerative medicine.